Towards a general kinetic model for the thermal oxidation of epoxy-diamine networks. Effect of the molecular mobility around the glass transition temperature. (November 2020) - Colin, Xavier; Essatbi, Fatima; Delozanne, Justine; Moreau, Gurvan
Highlights: A general kinetic model is developed for the thermal oxidation of epoxy-diamine networks. Oxygen transport properties are estimated from a compilation of literature data. Rate constants and formation yields are determined by reverse solving method. Molecular mobility affects strongly the bimolecular combinations of peroxy radicals and much less significantly the propagation of oxidation. Abstract: The kinetic model previously established for describing the thermal oxidation of polymethylenic substrates has been successfully generalized to a series of six epoxy-diamine networks (EPO-DA) characterized by very different glass transition temperatures. This model is derived from the so-called "closed-loop" mechanistic scheme which consists in a radical chain reaction initiated by the decomposition of hydroperoxides and propagating via the C-H bonds located in α of heteroatoms (N and O). The numerous model parameters were determined by applying a "step by step" procedure combining experiment and simulation. On the one hand, oxygen transport properties (i.e. coefficients of oxygen diffusion and solubility) were estimated from a compilation of literature data. On the other hand, rate constants and formation yields were determined by inverse solving method from the measurements of oxygen consumption and carbonyl build-up performed on six different EPO-DA networks between 25 and 200 °C and between 0.16 and 20 bars of oxygen partial pressure in our laboratory or in the literature. It was found that the molecular mobility mainly affects the rate constants of the elementary reactions involving the reactive species in the lowest concentration, i.e. peroxy radicals. In fact, the rate constant k6 of the apparent termination of peroxy radicals is reduced by about five orders of magnitude when passing from rubbery to glassy state due to the freezing of large amplitude cooperative molecular movements. In contrast, the rate constant k3 of the propagation of oxidation, involving peroxy radicals but also the polymer substrate, is only changed by one order of magnitude around the glass transition temperature. The introduction of the effect of molecular mobility into the Arrhenius laws of k6 and k3 allows building master curves and finally, proposing a single kinetic model for the whole family of EPO-DA networks.